PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS CERITA PENDEK - Wulandari, Jihan; Khaltsum, Ummu; Syamsul Alam, Andi (Almeera Education, 2024)
The primary issue addressed in this research is the application of the Problem-Based Learning (PBL) model to enhance the short story writing skills of fourth-grade students at SDN 127 Inpres Moncongloe. The use of the PBL model aims to facilitate students' understanding of the material and improve their ability to write short story texts, thereby increasing their overall proficiency. Through the PBL model, improvements can be observed in both the learning process and the outcomes. This study is conducted as Classroom Action Research (CAR) at SDN 127 Inpres Moncongloe. The research implementation is divided into two cycles, with each cycle consisting of two meetings. Data were collected through (1) tests and (2) observations during the learning sessions. Data analysis was performed using qualitative descriptive techniques. The criteria for success in this research were determined by observing positive changes in scores across each cycle. The success of this research is evaluated based on two criteria: the learning process and the learning outcomes. The findings of the research are as follows: First, the implementation of the PBL model significantly improves the quality of students' learning in writing short story texts. This is evidenced by enhanced learning processes, with students becoming more focused, active in group activities, and finding the learning of short story writing more enjoyable. Second, the use of the PBL model leads to improved learning outcomes in writing short story texts. From the first cycle to the end of the second cycle, all aspects and criteria of short story writing showed significant improvements. Based on the results of this research, it can be concluded that the application of the Problem-Based Learning model was successful in enhancing the short story writing skills of fourth-grade students at SDN 127 Inpres Moncongloe.